New World monkeys the evolutionary odyssey - Rosenberger, Alfred L. (Princeton University Press, 2020)
"This book is a broad synthesis of new world monkey evolution, integrating their unique evolutionary story into the bigger picture of primate evolution and Amazon biodiversity. Capsule For more than 30 million years, New World monkeys have inhabited the forests of South and Central America. Whether these primates originally came from Africa by rafting across the Atlantic or crossing overland from North America, they soon flourished. This book tells the story of these New World monkeys. Integrating data from fossil and living animals, it explores the evolution of the three major New World monkey lineages as well as how they fit into the broader story of primate evolution and Amazon biodiversity. After providing readers with necessary background in primate taxonomy and systematics, Rosenberger shows that the notion of adaptive zones is central to our understanding of primate evolution. The idea of adaptive zones can explain how radiations evolve, morphological adaptations appear, and communities form. From here, Rosenberger synthesizes what is known about New World monkeys' unique ecological adaptations, including those involving feeding and locomotion, as well as their social behaviour. The book's concluding chapters explore theories of how primates first arrived in South America and what their future looks like given the threat of extinction. Biography Internal Use Only Alfred L. Rosenberger is Professor Emeritus of Biological Anthropology at Brooklyn College. An expert on the origin and evolution of New World Monkeys, Rosenberger has contributed numerous articles in edited volumes and his work is published in journals such as Nature, Journal of Human Evolution and American Journal of Primatology . Audience The audience for this book is scholars and graduate students in biological/physical anthropolog and primatology, and to a lesser extent conservation biology, evolutionary biology, and behavioral ecology . Rationale - no copy text Other Relevant Info - no copy text"--